Strategic Silence: College Men and Hegemonic Masculinity in Contraceptive Decision Making. Issue 5 (October 2019) - Dalessandro, Cristen; James-Hawkins, Laurie; Sennott, Christie
Condom use among college men in the United States is notoriously erratic, yet we know little about these men's approaches to other contraceptives. In this paper, accounts from 44 men attending a university in the western United States reveal men's reliance on culturally situated ideas about gender, social class, race, and age in assessing the risk of pregnancy and STI acquisition in sexual encounters with women. Men reason that race- and class-privileged college women are STI-free, responsible for contraception, and will pursue abortion services if necessary. Since men expect women will take responsibility, they often stay silent about condoms and other contraceptives in sexual encounters—a process we term "strategic silence." Men's strategic silence helps uphold local constructions of hegemonic masculinity that prioritize men's sexual desires and protects these constructions by subtly shifting contraceptive and sexual health responsibility onto women. Our analysis demonstrates the importance of men's expectations of women for upholding constructions of hegemonic masculinity, which legitimate gender inequality in intimacy and are related to men's underestimation of the risks associated with condom-free sex.